2021
DOI: 10.36469/001c.26129
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Literature Review of the Epidemiology, Health-Related Quality of Life Impact, and Economic Burden of Immunoglobulin A Nephropathy

Abstract: Introduction: This systematic literature review analyzed published evidence on IgA nephropathy (IgAN), focusing on US epidemiology, health-related quality of life (HRQoL), and economic burden of illness.Methods: Using Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, Embase®, MEDLINE®, Cochrane, and Econlit (January 2010 to June 2020) were searched, along with relevant congresses (2017)(2018)(2019)(2020).Results: Of 123 epidemiologic studies selected for data extraction, 24 reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 65 publications
0
23
0
Order By: Relevance
“…Several studies suggested that PRKAR2A was associated with inflammatory pain and that antagonizing PRKAR2A offered a practical solution to controlling inflammatory pain [ 38 , 39 ]. A systematic literature review of IgAN has described that across 8 studies reporting health-related quality of life, pain and fatigue were the most reported symptoms [ 40 ]. In this study, decreased abundance of plasma PRKAR2 was observed among IgAN patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggested that PRKAR2A was associated with inflammatory pain and that antagonizing PRKAR2A offered a practical solution to controlling inflammatory pain [ 38 , 39 ]. A systematic literature review of IgAN has described that across 8 studies reporting health-related quality of life, pain and fatigue were the most reported symptoms [ 40 ]. In this study, decreased abundance of plasma PRKAR2 was observed among IgAN patients.…”
Section: Discussionmentioning
confidence: 99%
“…IgAN is the most common GN globally, and is more common in the East and Pacific Asian countries. 48 Patients typically present with microscopic or gross hematuria. Proteinuria is common, and is associated with progression of kidney disease.…”
Section: Kidney Pathology Potentially Related To Covid-19mentioning
confidence: 99%
“…Light microscopy shows moderate to diffuse cellular to fibrocellular crescents associated with ruptured Bowman’s capsule. 48 , 49 , 50 , 51 , 52 , 53 , 54 The degrees of glomerulosclerosis ranges from mild to severe. 72 ATI is common with inflammatory infiltrates in some cases, and tubulitis may be observed.…”
Section: Kidney Pathology Potentially Related To Covid-19mentioning
confidence: 99%
“… 3 A meta-analysis based on published United States (US) studies estimated an annual incidence of 1.29 per 100,000 people. 4 It occurs with the highest frequency in East Asians and Caucasians and is relatively rare in individuals of African ancestry. 5 IgAN is characterized by the formation and amplification of pathogenic immunoglobulin A (IgA) immune complexes that deposit within the glomeruli of the kidney, 2 , 6 , 7 and results in signs and symptoms including proteinuria (protein excreted in the urine), hematuria (blood in the urine), and hypertension.…”
Section: Introductionmentioning
confidence: 99%